Evaluating Therapeutic Efficacy of Cephalexin and PGF2α in the Management of Endometritis in Crossbred Cattle - Kumar Panigrahi, Sudeep; Behera, Himanshu; Dhar, Supriya; Mishra, Madhusmita; Sethy, Kamdev; Kumar Patra, Bijay (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Twenty-four cows diagnosed with subclinical endometritis (SCE) were divided into four equal groups: Group I (Cephalexin intrauterine  infusion), Group II (intramuscular PGF2α), Group III (combined Cephalexin and PGF2α), and Group IV (untreated control). Diagnostic  parameters included were haemato-biochemical, enzymatic, ultrasonographic and cytological assessments before treatment and after  treatment (i.e. next estrus). White side test (WST) with a 45.83% positivity rate and endometrial cytology with PMN cell count exceeding  5% was found. PMN cell count decreased significantly, with Group III from 13.33 ± 0.67% to 2.50 ± 0.55% post-treatment. Ultrasonography  indicated reductions in intraluminal fluid and endometrial thickness in treated groups. Post-treatment haemoglobin and TLC levels  were highest in Group III with values of 11.42±0.19 g/dL and 10.15±0.10 × 10³/µL, respectively. Biochemical analyses showed significant  increase in total protein and globulin levels in treated groups. Enzymatic activity of ALT and AST decreased significantly in Groups I and  III, reflecting reduced uterine inflammation. Progesterone levels remained stable across all groups indicating normal luteal function. The  findings highlight the efficacy of the combined Cephalexin and PGF2α treatment protocol (Group III) in normalizing altered haemato biochemical profile and managing SCE in bovine.
Keywords: Cephalexin; Crossbred cattle; Endometritis; PGF2α